Supervision essentials for the feminist psychotherapy model of supervision - Brown, Laura S. (Clinical supervision essentials series., 2016)
This book offers a theoretically grounded yet practical approach to supervision based on the principles of feminist psychotherapy. Feminist therapy supervision challenges trainees and supervisors alike to engage with difficult questions about bias, and ways in which power distributes itself in the contexts of education, psychotherapy, and supervision itself. Chapters examine the impact of systemic hierarchies, and stress the importance of thinking critically about dominant cultural norms in psychotherapy and elsewhere. Includes a synthesis of the literature on feminist therapy and theory, as w.